2015
DOI: 10.1128/aem.02484-15
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Aerosolized Bacterial Viruses to Relative Humidity and Temperature

Abstract: The use of aerosolized bacteriophages as surrogates for hazardous viruses might simplify and accelerate the discovery of links between viral components and their persistence in the airborne state under diverse environmental conditions. In this study, four structurally distinct lytic phages, MS2 (single-stranded RNA [ssRNA]), 6 (double-stranded RNA [dsRNA]), X174 (singlestranded DNA [ssDNA]), and PR772 (double-stranded DNA [dsDNA]), were nebulized into a rotating chamber and exposed to various levels of relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 23 publications
3
54
0
1
Order By: Relevance
“…We confirmed the sensitivity, linearity, and specificity of the selected primer-probe set even in the presence of other environmental microbes. Using this quantitative PCR system and culture assay, we performed a behavior analysis of a phage aerosol at different levels of humidity, which is known to affect the viable number of airborne phi-X174 phages Nakanishi et al, 2012;Verreault et al, 2015 .…”
Section: Quantification Of the Viral Amount Using Real-time Pcr Qpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed the sensitivity, linearity, and specificity of the selected primer-probe set even in the presence of other environmental microbes. Using this quantitative PCR system and culture assay, we performed a behavior analysis of a phage aerosol at different levels of humidity, which is known to affect the viable number of airborne phi-X174 phages Nakanishi et al, 2012;Verreault et al, 2015 .…”
Section: Quantification Of the Viral Amount Using Real-time Pcr Qpcrmentioning
confidence: 99%
“…We selected a primer-probe set, set A, for PCR to robustly quantify phi-X174-specific airborne particles without being adversely affected by UV. Duchaine s research group had used another primer-probe set, set B Turgeon et al, 2014;Verreault et al, 2015;Turgeon et al, 2016. Ho et al 2016 had reported that the log reduction by UV of phi-X174 gene copies increased as the specific amplicon length for PCR increased.…”
Section: Behavior Analysis Of the Phage Aerosol At Different Levels Omentioning
confidence: 99%
“…27 The resistance of various phages to environmental stresses (RH, ultraviolet [UV], temperature, and aerosol duration) was studied, and it was shown that the response to stresses varied between the various models. 28 Phage MS2 has been the most broadly used surrogate in aerosol studies and is used mostly in biodefense to predict the fate and transport of biothreat agents. 29 Table 1 presents the phage models used and validated.…”
Section: Phages As Models For Airborne Virusesmentioning
confidence: 99%
“…Environmentally controlled aerosol-aging chambers are designed to simulate environmental stresses that are imposed on microbial aerosols in order to understand the role of environmental parameters, such as temperature, UV, and RH, on the fate of airborne infectious agents. 28 Aerosols can remain airborne for prolonged periods in rotating chambers 31 because these particles remain suspended in a rotating mass of air. The gravitational forces exerted on the particles are countered by centrifugal forces created by the rotation of the drum.…”
Section: In Vitro Assessment Of Microbicidal Agents and Processes Formentioning
confidence: 99%
See 1 more Smart Citation